Web-Based Letter Management Information System in East Kalimantan Plantation Department - Istiqomah; Suswanto; Ida Maratul Khamidah (TEPIAN, 2021)
The constraints that exist in a system that is run manually, include the large amount of data that must be processed, the complexity in processing data, the limited time used in processing data, and various types of data. Likewise, in an office of the Plantation Service in East Kalimantan Province, processing correspondence is still done manually. This application uses a system by entering the type of letter to find a list of incoming and outgoing mail to make it easier for operators at the Plantation Service in East Kalimantan Province. In this program, the operator must enter first to access data from incoming messages and announcements. Therefore, this application is expected to improve the previous system and make work easier so that it can shorten the time so that work efficiency increases and makes it easier for operators to process data.Based on the results of observations in the form of an interview with an employee of the Data Information Service Center (PPID) at the Plantation Office of East Kalimantan Province, it was stated that there was no system or application. Correspondence services at the Plantation Office of East Kalimantan Province have been running well, but all processes are still manual and use a lot of paper. This application is also a form of concern for paper, where paper usage is starting to be reduced. All data and documentation are presented in digital or paperless form.Referring to the results of these observations, we need a web media capable of displaying correspondence with detailed information. With this web, it is expected to be useful for employees. In addition, it can assist the East Kalimantan Provincial Plantation Office in providing correspondence information.With the Correspondence Management Information System website, it is hoped that it will be useful for employees at the Plantation Office of East Kalimantan Province in processing letter data so that they can work effectively and efficiently in the process